(untitled) (Zaporizhzhia Historical Review, 2021)
The article gives the analysis of charity activity and role of the orthodox clergy as well as church associated bodies (monasteries, parish trustees and fraternities) in public education developing within Poltava Diocese during the XIXth century. The main aspects of their activity were to open, develop and finance the church maintained schools, help orphan pupils and pupils from the poorest families, set up libraries at churches and provide teaching by parish clergy on charitable basis.